PSICANÁLISE E CIDADE: PERSPECTIVAS DO FAZER DO ANALISTA NA SAÚDE MENTAL - Jacyntho, Barbara; Brito, Bruna; Mendes Venâncio Da Costa, Laísa (LINKSCIENCEPLACE, 2026)
Based on the assumption that different social actors inhabit the city, it‟s defended that the analyst assumes a praxis of "citizen analyst", a concept proposed by Éric Laurent. From this, the article proposes to discuss aspects of the psychoanalytic clinic in the city and practices that go beyond the classic model of the clinical setting. We search the tracings through which the clinic is drawn in the city from clinical reports that report the existence of a relationship between the two aspects. In order to do so, we study the development of cities from the Middle Ages to the present day. Next, we will articulate the ideas presented by the psychoanalyst Christian Dunker, who marks new configurations in brazilian urban geography, by the creation of condominiums and by Freud in his work «Civilization and its Discontents» in which the author discusses the different forms of human suffering.